Real Time Implementation of Air Quality Monitoring System using IoT and Ubidots - Satyanarayana, P.; Narmadha, R. (International journal of recent technology and engineering, 2019)
Nowadays air pollution is main distress for the human being, as it is demeaning the green health and inhale the pollutant air is hazardous for the health of the human being. Because of bad things of the air pollution on the human being, the demand for the improvement of enormous quality air monitoring systems has been in superior demand. The air pollution monitoring system detect the concentration levels of air pollutants and the analysis of the collected information is required for the policymakers to take necessary and proper steps to decrease the level of air pollution for the wellbeing of their citizens. The air pollution monitoring mechanism implemented in this paper is based on Arduino UNO board and IoT platform. The Arduino UNO board interface with Ubidots platform using ESP8266 Wi-Fi Module. Generally in cities Wi-Fi hotspots are available at many locations, so the air pollution monitoring mechanism can be easily set up at any hotspot. Ubidots is one of the smart IoT platforms. Sensor data is displayed in terms of ppm with different levels and different events in IoT device. The detecting of information and deliver it to the Ubidots server through Wi-Fi module is guided by the Arduino Sketch. The Arduino sketch is composed, compiled and supplied to the Arduino board using Arduino IDE.